Peningkatan Kapasitas Masyarakat dalam Mengenali Tanda dan Gejala Tuberkulosis melalui Intervensi Edukasi - Mega Arianti Putri; Kuswanto Kuswanto; Erny Rohmatus Saadah (Lembaga Pengembangan Kinerja Dosen, 2026)
Tuberculosis (TB) remains a significant public health concern due to its widespread occurrence and potential for transmission. Insufficient public awareness regarding TB symptoms and transmission pathways may delay early detection and increase the risk of disease spread within the community. This community service program was designed to enhance community understanding of tuberculosis signs and symptoms through health education. The activity involved 36 community members, predominantly adult women. Educational interventions were delivered through lectures, interactive discussions, question-and-answer sessions, and the distribution of informational leaflets. Participants’ knowledge was assessed using pre-test and post-test evaluations. The findings demonstrated an improvement in knowledge following the educational intervention, as reflected by an increase in the average score from 58.6 before the program to 84.2 afterward. Participants gained a better understanding of TB symptoms, modes of transmission, the importance of early diagnosis, and preventive measures applicable in daily life. In addition, the program fostered greater awareness and encouraged community involvement in tuberculosis prevention and control efforts. These findings suggest that health education is an effective approach to strengthening community health literacy and supporting tuberculosis control initiatives.